Immune Pathogenesis and Risk Factors Associated with Leprosy (Hansen's Disease) - Alfira Safitri; Ni Luh Putu Eka Widya Ananta Putri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Leprosy (Hansen’s disease) is a chronic infectious disease caused by Mycobacterium leprae and remains a significant public health problem in many endemic countries, including Indonesia. This study aimed to review the immune pathogenesis and associated risk factors of leprosy based on recent scientific evidence. A narrative literature review was conducted using articles retrieved from PubMed, ScienceDirect, Google Scholar, and World Health Organization (WHO) databases, published between 2015 and 2025. The literature search applied predefined inclusion and exclusion criteria, and study selection was performed through title, abstract, and full-text screening. A total of 4,791 records were identified from all databases, and 31 articles were included in the final analysis. The selected literature was synthesized using a descriptive approach. The clinical spectrum of leprosy is determined by the interaction between M. leprae and the host immune response. Tuberculoid leprosy is associated with a dominant T helper 1 (Th1) response characterized by increased interferon-gamma (IFN-γ) production and enhanced macrophage activation, while lepromatous leprosy is associated with a T helper 2 (Th2)-dominant response characterized by elevated interleukin-4 (IL-4), interleukin-5 (IL-5), and interleukin-10 (IL-10), leading to ineffective bacterial clearance. Emerging evidence also highlights the roles of T helper 17 (Th17) and regulatory T (Treg) cells in immune modulation and disease progression. In addition, host and environmental factors such as age, sex, history of contact, housing conditions, personal hygiene, and Bacillus Calmette–Guérin (BCG) vaccination status contribute to susceptibility and transmission.